Peran Mediasi Brand Image Pada Green Promotion, Environmental Consciousness, Information Credibility Terhadap Purchase Decision - Qisthi Larasati; Wisnalmawati Wisnalmawati; Dyah Sugandini (LPPM Universitas BSI, 2021)
ABSTRACTThis study aims to analyze the effect of green promotion, environmental consciousness, information credibility on purchase decisions mediated by brand image on environmentally-friendly cosmetic products The Body Shop in Yogyakarta. The variables used in this study are green promotion (X1), environmental consciousness (X2), information credibility (X3) purchase decision (Y), and brand image (Z). The population in this study are consumers who use The Body Shop products in Yogyakarta. The total sample in this study was 100 respondents using the convenience sampling technique or also known as accidental sampling and the data collection method using a questionnaire. The data analysis used was SEM (Structural Equation Model) analysis with the SMART PLS 3.2.7 program. By testing the hypothesis, the results of the analysis show that green promotion, environmental consciousness, information credibility has a positive effect on purchase decisions on The Body Shop products in Yogyakarta, and brand image can mediate the variables of green promotion, environmental consciousness, information credibility on purchase decisions. The suggestions for further researchers are because in this study there are still limitations so that further researchers are expected to be able to research with other variables and need to use a wider and more diverse range of respondents to obtain more varied results that can affect purchasing decisions. Keywords: Brand Image, Environmental Consciousness, Green Promotion, , Information Credibility, Purchase Decision.